Pangawikan Pribadi: The Core of Healing in Javanese Counseling - Sarwono, R Budi; Mappiare, Andi; Hambali, IM; Ramli, M (Universitas Negeri Padang, 2024)
This qualitative research proves that a typical Javanese systematic dialogue called Junggringan can improve an individual's cognitive structure, change their awareness, and then bring about changes at the behavioral levels. These changes then bring individuals out of problems. In Javanese terminology, this condition is called pangawikan pribadi. This paper aims to obtain an indigenous counseling model relating to Junggringan. This research involved 12 participants as the research subjects. By following the Junggringan dialogue, they succeeded in reaching the peak condition, where individuals realize errors in thinking and realize the absence of awareness, which then encourages maladaptive behavior. Acceptance of erroneous ways of thinking and lack of awareness drives individuals to an inner state of extraordinary relief. This peak experience is called Pangawikan Pribadi. With Pangawikan Pribadi, it is easier for individuals to find the solution. This is the essence of Javanese Counseling.